Tau Therapeutic Strategies for the Treatment of Alzheimer's Disease - Churcher, Ian (Current Topics in Medicinal Chemistry, 2006)
The two classical pathological hallmarks of Alzheimer's disease are deposits of aggregated β-amyloid (Aβ ) peptide and neurofibrillary tangles composed of hyperphosphorylated tau protein. In addition to Aβ pathology, an invariant trait of Alzheimer's disease, disruption of tau processing is a necessary event in the neurotoxic cascade which eventually leads to neuronal death and subsequent dementia. Tau is a neuronal, microtubule-bound protein which becomes hyperphosphorylated as a result of an imbalance of the kinase and phosphatase activities which normally tightly regulate its phosphorylation. In addition to this pathogenic hyperphosphorylation, tau dissociates from microtubules and selfaggregates to form insoluble oligomers which progress to the macroscopic tangles evident in post mortem Alzheimer's disease tissue. Subsequent toxicity may ensue either as a direct toxic effect of free tau oligomers or as a result of altered microtubule-dependent processes. In order to intervene pharmacologically in this disease process, much effort has been expended in order to identify and inhibit the kinases responsible for pathogenic hyperphosphorylation and many candidate kinases have been investigated including glycogen synthase kinase (GSK-3), cyclin-dependant kinase-5 (Cdk-5), MAPK family members (extracellular signal-regulated kinases 1 and 2 [Erk-1 and 2], MEK [MAP kinase kinase], c-Jun NH2- terminal kinases (JNKs) and p38), casein kinase, calcium calmodulin-dependant kinase II (CaMK-II), microtubule affinity regulating kinase (MARK), protein kinase A (PKA / cAMP-dependant protein kinase) and others. Focus has also fallen upon the role of the phosphatases responsible for dephosphorylation of tau. This review will describe the tau-related etiology of Alzheimer's disease and other tauopathies as well as the therapeutic strategies to inhibit the hyperphosphorylation of tau.
Keywords: GSK